Post-Keynesian economics How to move forward - Engelbert Stockhammer; Paul Ramskogler (Intervention. European Journal of Economics and Economic Policies, 2009)
Post-Keynesian Economics (PKE) is at the crossroads. Post-Keynesians (PKs) have become effectively marginalized; the academic climate at universities has become more hostile to survival and the mainstream has become more diverse internally. Moreover, a heterodox camp of diverse groups of non-mainstream economists is forming. The debate on the future of PKE has so far focussed on the relation to the mainstream. This paper argues that this is, in fact, not an important issue for the future of PKE. The debate has so far strangely overlooked the dialectics between academic hegemony and economic (and social) stability. In times of crisis the dominant economic paradigm becomes vulnerable. The important question is, whether PKE offers useful explanations of ongoing socio-economic transformations. PKE has generated valuable insights on core areas such as monetary macroeconomics and medium-term growth theory, but it offers little on important real world phenomena like the globalisation of production and social issues like precarisation and the polarization of income distribution or ecological challenges like climate change. It is these issues that will decide the future of PKE.
Keywords: B20; B50; B59; E12; 330; post-Keynesian economics; mainstream economics; heterodox economics; neo-liberalism